2016
DOI: 10.1007/s13277-016-5358-6
|View full text |Cite
|
Sign up to set email alerts
|

The biology of extracellular vesicles with focus on platelet microparticles and their role in cancer development and progression

Abstract: Extracellular vesicles (EVs) are a heterogeneous group of structures which can be classified into smaller in size and relatively homogenous exosomes (EXSMs)—spherical fragments of lipid bilayers from inner cell compartments—and bigger in size ectosomes (ECSMs)—a direct consequence of cell-membrane blebbing. EVs can be found in body fluids of healthy individuals. Their number increases in cancer and other pathological conditions. EVs can originate from various cell types, including leukocytes, erythrocytes, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 124 publications
1
89
0
1
Order By: Relevance
“…Because triple peptidase positive m/lEVs were negative for Annexin V, the mechanism of budding from cells may not be dependent on scramblase. [25] Platelet-derived m/lEVs are the most abundant population of extracellular vesicles in blood, and their presence [11] and connection with tumor formation were reported in a recent study [29]. In our study, platelet-derived EVs were observed in healthy subjects and had the highest abundance of Annexin V-positive EVs.…”
Section: Discussionsupporting
confidence: 72%
“…Because triple peptidase positive m/lEVs were negative for Annexin V, the mechanism of budding from cells may not be dependent on scramblase. [25] Platelet-derived m/lEVs are the most abundant population of extracellular vesicles in blood, and their presence [11] and connection with tumor formation were reported in a recent study [29]. In our study, platelet-derived EVs were observed in healthy subjects and had the highest abundance of Annexin V-positive EVs.…”
Section: Discussionsupporting
confidence: 72%
“…The formation of microparticles is a process similar to cytokinesis . It involves the disruption of the calcium‐dependent actin cytoskeleton and the proteolysis of actin bonds from plasma membrane phospholipids . This induces the membrane to bleb spontaneously because of the pressure difference .…”
Section: Features Of Pevsmentioning
confidence: 99%
“…(24) It involves the disruption of the calcium-dependent actin cytoskeleton and the proteolysis of actin bonds from plasma membrane phospholipids. (43) This induces the membrane to bleb spontaneously because of the pressure difference. (24,43) However, other mechanisms have been implicated, such as membrane curvature proteins, lipid membrane reorganization, and actin-myosin contraction elicited through guanosine triphosphate-binding protein, adenosine diphosphateribosylation factor 6, or rho-associated protein kinase 1 signaling.…”
Section: Features Of Pevsmentioning
confidence: 99%
See 1 more Smart Citation
“…ВВ способны переносить разнообразные рецепто-ры (например, тромбоцитарные интегрины) на поверх-ность раковых клеток путем слияния с ними, индуци-ровать активацию киназных каскадов (например, путей митоген-активируемой протеинкиназной сигна-лизации и протеинкиназы B), стимулировать экспрес-сию металлопротеиназ матрикса и сосудистого эндо-телиального фактора роста, подавлять апоптоз, вызывать хемотаксис и способствовать появлению метастазов, а также развитию множественной лекарст-венной устойчивости (путем переноса одних мембран-ных молекул или индукции экспрессии других) [47]. Сейчас эта область исследований бурно развивается.…”
Section: Fig 6 Formation Of Microvesicles During Activation Of Platunclassified